Pengaruh Model Pembelajaran Discovery Learning Berbasis Numbered Head Together Terhadap Hasil Belajar Matematika Ditinjau dari Komunikasi Matematika Siswa Kelas VII SMP Negeri 2 Sawit - Utami, Dyah Rizki; , Dra. Nining Setyaningsih, M.Si (2017)
The purpose of this study to examine (1) the different effect of the learning model Discovery Learning based Numbered Head Together toward mathematics earningachievement of student, (2) the different effect of mathematics ommunication toward mathematics learning achievement of student, (3) the interraction between the learning model dan mathematics communication toward mathematics learning achievement of student. Quantitative research with a quasi-experimental design. Population dan sample junior high school 2 Sawit seven grade student. The sampling technique using cluster random sampling. The data collection technique using the test metds, questionnaire dan documentation. Data were analyzed using analysis of variance of two paths with difference cell. The results of the study significant's level 5 % is (1) there is a significant influence of the learning model Discovery Learning base Numbered Head Together toward mathematics learning achievement of student, (2) there is significant influece mathematics learning achievement of student, (3) there is no interraction between the learning model and mathematics toward communication mathematics learning achievement of student.